The use of biomarkers for assessing effects of pollutant stress on fish species from a tropical river in Southeastern Brazil (Acta Scientiarum. Biological Sciences, 2017)
Biomarkers are measurements within an organism that respond to environmental effects and are used as tools in bioassessment programs since they reflect physiological changes induced by exposure to pollutants. The hepatosomatic index (HSI) and the condition factor (CF) in three fish species Geophagus brasiliensis, Hypostomus affinis and Hypostomus auroguttatus were used to assess effects of pollutant stress in a tropical river during two seasons (dry and wet). Fish from the least disturbed sites had the lowest condition factor (CF) and the lowest HSI, whereas those from sites near pollutant discharges had the highest CF and HSI. Higher HSI and lower CF occurred during the dry season. It is suggested that species adapted to stressful conditions take advantage on food availability from organic loads or unoccupied niches by lesser tolerant species, increasing CF. We concluded that higher HSI values were directly associated with environmental stress whereas the higher CF values are related to availability of food resources derived from organic loads or other sources. CF and HSI are simple and cost-effective, thus suitable as routine screening tools in pollution monitoring, but caution should be taken in relating changes in physiological measurements and any specific pollutant to prevent misinterpretation.